“Dead Girl-Bag”:: The Janet Smith Case as Contaminant in Sky Lee’s Disappearing Moon Café - MacDonald, Tanis (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
In her 1990 novel Disappearing Moon Café, Sky Lee capitalizes upon the slipperiness of public and private historical narrative in order to examine the cultural codes of race and gender in 1920s Vancouver. Lee uses the unsolved 1924 Janet Smith murder case as a correlative to the fictional Wong family's history, creating a counternarrative of Chinese-Canadian history that questions historical master narratives. Smith's murdered body functions both as a contaminant that infects the Wong's family history, and as a catalyst that inspires their familial regeneration and prosperity. The novel's staggered narrative also emphasizes the ways in which the Wong family's history resists completion and dismantles the generational story's traditional trope of defining the self through family. If Smith's death signalled the need for greater social and cultural tolerance, then her reinstatement as a referent in Lee's novel demands a broader perspective of Canadian history and citizenship.